Investigating the impact of different sport trainings on particulate matter resuspension in a sport center using well-characterized reference instruments and a low-cost monitor - Amouei Torkmahalleh, Mehdi; Kabay, Karakat; Zhanabayeva, Meruyet; Mohiuddin, Obaidullah; Obaidullah, Madina; Gorjinezhad, Soudabeh (Science of The Total Environment, 2018)
Abstract The present study investigated the exposure of teenagers, adults, and students to PM1, PM2.5, PM4, PM10, particle number concentration at two sport facilities of Nazarbayev University including Gymnastics Hall and Multi-purpose Hall. Measurements were conducted during variety of sport training sessions including soccer, basketball, volleyball, Mixed Martial Arts (MMA), boxing, table tennis, etc. A low-cost instrument, Dylos was employed to compare its performance against two TSI instruments. In overall, the Dylos showed acceptable peaks when the source of particle resuspension was present. However, no correlation was observed between Dylos data and Dusttrak fine and coarse particle data. The average PM2,5 and PM10 concentrations were found to be below the WHO limits. The number of participants during the training sessions and sports involving balls including basketball, soccer and volleyball were the two factors responsible for the observed increased particle resuspension.
Keywords: Particulate matter (PM); Physical activity; Sport center; Exposure; Low-cost instruments